Studi Inovasi Strategi Kebijakan Percepatan Pencapaian Swasembada Kedelai Indonesia Tahun 2035 - Artinus Hulu (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2023)
The high rate of consumption and demand for soybeans without an increase in production has forced the Indonesian government to always import soybeans. Import policy must be given special attention to suppress price increases and make the rate of MSMEs continue to grow well. It’s important to formulate policy designs to accelerate the fulfillment of domestic soybean supply in Indonesian. Method research uses a qualitative method with a literature review from many literature and data sources which is then made a policy-making model based on incremental theory. The results make indicate that self-sufficiency in soybeans may be realized, if long-term arrangements are made for several things, namely expanding the area, subsidizing soybean prices, import regulations and setting fair soybean import tariffs, developing the soybean jabalsim subsystem with innovation, controlling the rate of population, and the improvisation with technology innovation. Steps to recommend policies by setting import tariffs using an open and close system following domestic production conditions, forming small analysis teams that observe, assist and work directly on the sub-section of the soybean issue, synergy and harmony of legal products within the central government related to excise tariffs imports according to WTO standards and rigid subsidized pricing below import prices. BULOG needs to regulate the trade system with digital public service innovations based on E-Agriculture Government. In addition, the government needs to partner with the private sector to increase domestic production, provide social-health insurance protection and crop insurance to soybean farmers and assist with the implementation of smartfarming agriculture.